24. EVALUATION OF TREATMENT OF CHRONIC MALLET FINGER DEFORMITY WITH A MODIFIED PALMARIS LONGUS TENDON GRAFT THROUGH A BONE TUNNEL AT THONG NHAT HOSPITAL - HO CHI MINH CITY (Vietnam Journal of Community Medicine, 2024)
Purpose: Evaluation of treatment of chronic mallet finger deformity with a modified palmaris longus tendon graft through a bone tunnel. Subject and methods: Prospective study with 7 patients with chronic mallet finger deformity are treated with a modified palmaris longus tendon graft through a bone tunnel. Results: Average age was 37.14, gender was mainly male with male/female ratio of 2.5. The time from injury to surgery is 8.71 months with the main cause being labour and daily life accidents, the most common type of injury is type 1 according to Doyle 1993 with a rate of 42.85%, the shortest follow-up time 3 months and the longest was 8 months with results ranging from good to very good reaching 100%, only 1 case of a patient having a superficial surgical wound infection. Conclusion: Surgical treatment of chronic mallet finger deformity with modified long palmar tendon graft through bone tunnel brings very positive results.
Keywords: Mallet finger, modified, bone tunnel, tendon graft.